Tari Baris Cina Sebagai Referensi Penciptaan Karya Seni Lukis - Divayana, I Putu; Pemayun, Tjokorda Udiana Nindhia; Tjokropramono, I Gede Yosef (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
This independent project thesis raises the Chinese Baris Dance as a Reference for the Creation of Painting Art works, starting from an interest in the visuals of the Baris Cina dance which is unique and different from the visuals of the Baris dance in general. This fueled the urge to bring the visuals of the Chinese Baris dance by combining certain techniques and references to achieve the desired meaning. The problem being faced is how to work on the visuals of the Chinese Baris dance to represent the ideas and meanings that you want to materialize so that they are still packaged attractively. The benefits and objectives of this thesis are to increase the existence of the Chinese Baris dance, and to increase the author's understanding of the Chinese Baris dance. To answer what is the goal of this work, the methods used are exploration, improvisation, and forming. With elements of fine art, and through the stages of exploration, improvisation or experimentation and formation, and combined with ideas and concepts so as to create 6 works entitled: 1) "Freedom", 2) "Desire", 3) "Leader", 4) "Surge", 5) "Dark Fall", 6) "Circle of Harmony". In creating works, the author combines several techniques to references from several artists. By combining the techniques obtained at the Art kenyem studio and the placement of objects typical of Sugiyo Dwiarso, we hope to produce innovative works and are expected to produce novelty.In the end, it can be concluded that dance, especially the Chinese Baris dance, is very worthy to be appointed as a reference that can be developed and will become an innovative work. With the creation of this work, it is hoped that it can convey messages and meanings as well as give the author a new style or identity.